Mengenal Tugas dan Skill Seorang Front End Development - Sofyan Mufti Prasetiyo; Hapid Hidayat; Khoirun Nurul Musthofa; Malik Ibrahim Nur (CV. Multi Kreasi Media, 2023)
The development of technology in the digital era is currently experiencing very rapid progress, one of which is the internet. The internet is a repository of data and information needed by people from various professional fields, ranging from education, entertainment, business, health, sports and so on. With the internet, people can find the information they need through the website easily as long as there is a connection. The use of the website is one of the marketing, sales and service media for a business due to low costs, ease of access and efficiency because it can be accessed within 24 hours. On the website there are various types of work, one of which is Front End development, which is tasked with managing the appearance of a website that will be seen directly by users, the appearance of a website can be adjusted using CSS and also HTM, where HTML is the language used. in making websites while CSS is a programming language that can be used to define how a markup language is displayed on a media where one of these markup languages is HTML. As well as there are several methods that are commonly used on a website, for example, the waterfall method and also the agile method.